The Nyadran Tradition Based on Ethnoscience as the Local Wisdom of the Balongdowo Community of Sidoarjo - Handika Tusuka Putra; Utama Alan Deta; Setyo Admoko (Journal of Ethnophysics, 2026)
This study uncovers the hidden physics within the Nyadran tradition, an Indonesian ritual of ancestral homage. Moving beyond formulas, we employ an ethnoscience lens to reveal how this enduring local wisdom actively preserves and demonstrates core scientific principles. The research method used is descriptive qualitative in this case using journals with various primary data and interviews as secondary data in the data collection process. It is known that the stages of the Nyadran tradition can be analyzed using the concept of physics. The research results obtained are the preparation stage there is an optical concept at the time of installing the lights, the departure stage is the concept of displacement and equilibrium of rigid bodies and land winds, the stage of disposal of a chicken and larung offerings is the concept of floating objects from Archimedes' law, the stages of pilgrimage to Dewi Sekardadu's tomb are displacement, the stages of searching for kupang have the concepts of effort and energy, the stages of returning home have the concepts of displacement and sea breeze. Our findings illuminate the Nyadran not merely as a cultural practice, but as a living, applied physics lesson, offering a powerful model for contextualizing science education and appreciating the ingenuity embedded in tradition.